(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
This research explores consumer resistance to smartphone innovation in the Erbil/Iraq, uncovering several significant findings. The main goal of the study was to identify the consumer characteristics that influence this resistance and its implications. For smartphone manufacturers, marketers, representatives, and researchers, this study offers a comprehensive understanding of consumer behavior and resistance to technological progress. The results can guide targeted strategies to overcome barriers, improve product development, and increase market share. The study contributes to our understanding of innovation resistance in the unique context of the Erbil/Iraq, highlighting the importance of conducting thorough investigations in similar circumstances. In light of the findings of the demographic survey, a significant portion of respondents were young people, supporting the widely held belief that young individuals are more likely to adopt new technology. However, the study emphasizes that age is not the sole determinant of resistance to innovation. The diminished impact of income, marital status, and gender on resistance indicates a complex interplay of factors. Conversely, a higher level of education was associated with a greater likelihood of embracing smartphone innovation. The study delved into various aspects of innovation and revealed that self-efficacy, motivation, complexity, perceived risk, and expectations of a superior product all significantly influenced consumer resistance. Resistance showed a negative correlation with self-efficacy as a psychological trait, suggesting that individuals with higher levels of self-efficacy were less resistant to smartphone innovation. Conversely, higher levels of complexity, perceived risk, expectations of a better product, and motivation were linked to increased resistance, highlighting the crucial role of behavioral and psychological characteristics in shaping consumer attitudes towards innovation. Relative advantage did not appear to have a significant influence, while compatibility and attitudes towards current products were deemed insignificant predictors of resistance. These findings underscore the intricate nature of innovation resistance and demonstrate that socio-demographic traits alone are insufficient as predictors. Consumer resistance is largely shaped by psychological elements such as self-efficacy, motivation, expectations, complexity, and perceived risk.